Exceptions to the rules of intestacy in the former Yugoslavia (Slovenia, Macedonia, Montenegro, Republic of Srpska) - Vidić Trninić, Jelena (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
The author focuses on inheritance position that relatives, spouse and concubinage partner as intestate successors have in the laws of the countries of the former Yugoslavia (Slovenia , Macedonia and Montenegro ) as well as the entity of Bosnia and Herzegovina – the Republic of Srpska law, in cases when a corrective to ordinary rules of succession in certain intestacy classes applies, that is in case of application of the so-called exceptions to the rules of intestacy. The importance given to the fact of kinship (that is, the particular category of kins), marriage and concubinage  in each of these laws may be observed based on the way each of these laws approach the regulation of a number of questions related to this issue, from the circle of heirs whose intestacy share  can be increased or decreased, the existence of reciprocity in terms of the possibility to increase or decrease the shares of intestate successors covered by this possibility, as well as regarding the particular way (in terms of the type of inheritance authority) and the possible scope of increasing or decreasing the share of a particular heir. Therefore, all of these questions present the subject of analysis of this study which aims to determine the intensity of the changes in the hereditary position of certain intestate successors with respect to the one that they have upon application of the ordinary rules of intestacy (which was a subject of analysis of the previous article) in each of these laws. The purpose of the study is also to point out the advantages and some of the remaining weaknesses of the existing legal provisions in the relevant laws, and ultimately, to note the different and similar or even identical solutions adopted by the mentioned group of legislations in regulating this matter .